2022
DOI: 10.3390/ijerph20010718
|View full text |Cite
|
Sign up to set email alerts
|

Distorted Body Image and Mental Pain in Anorexia Nervosa

Abstract: (1) Background: Body image is being defined as the picture of our own body in our mind with its size and shape, and with a perceptive and attitudinal evaluation of this body. It appears to be a complex clinical construct predisposing an individual to developing and maintaining anorexia nervosa (AN), as well as having considerable impact on prolonging the duration of this illness and its relapse risk. The aim of the research work was to assess whether the symptomatology of eating disorders, level of depression,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Furthermore, previous authors suggested that adolescents with better parent-adolescent relationships presented a lower probability of suffering from body dissatisfaction [47]. Body disappointment is a complex risk factor which may predispose to anorexia development, maintaining and lengthening illness [48,49]. Previous researchers have pointed out how anorexia patients can be inclined to overvalue their body size, more specifically controversial parts such as hips, buttocks, abdomen and arms [50].…”
Section: Family and Anorexiamentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, previous authors suggested that adolescents with better parent-adolescent relationships presented a lower probability of suffering from body dissatisfaction [47]. Body disappointment is a complex risk factor which may predispose to anorexia development, maintaining and lengthening illness [48,49]. Previous researchers have pointed out how anorexia patients can be inclined to overvalue their body size, more specifically controversial parts such as hips, buttocks, abdomen and arms [50].…”
Section: Family and Anorexiamentioning
confidence: 99%
“…Previous researchers have pointed out how anorexia patients can be inclined to overvalue their body size, more specifically controversial parts such as hips, buttocks, abdomen and arms [50]. As a consequence, anorexia patients suffer different emotions such as anxiety, disapprobation, guilt and social withdrawal, increasing their discomfort [48]. Thus, it should be considered how powerfully parental influence may affect anorexia progress.…”
Section: Family and Anorexiamentioning
confidence: 99%
“…On the other hand, individuals who suffer from anorexia nervosa exhibit intense fear of gaining weight, food restrictions to prevent weight gain, and dissatisfaction with body weight and shape [19]. Individuals who have both disorders show decreased self-esteem, increased anxiety about appearance, social isolation, and eating behavior disorders [20,21].…”
Section: Body Weightmentioning
confidence: 99%
“…Possibly related to nutritional deficiencies (Casper et al, 1980;Beumont et al, 1997;McCue, 2010;Miao et al, 2015) Possibly related to nutritional deficiencies (Franklin et al, 1948;Tucker, 2006;McCue, 2010) Hoarding/stealing food Possibly a survival strategy (Crisp et al, 1980;Yao et al, 2017) Possibly a survival strategy Tucker, 2006) Body image Distorted body image (Ciwoniuk et al, 2022) Distorted body image (Tucker, 2006) Self-injurious/mutilation behavior Some engage in self-mutilation (Crisp, 1984bYaryura-Tobias et al, 1995 Some engage in self-mutilation (Tucker, 2006) Libido A dramatic decrease in sexual-related interests/activities (Crisp, 1967;Price et al, 2020) A dramatic decrease in sexual-related interests/ activities In a Randomized Control Trial (RCT), Bergh et al (2002) assigned 13 ANs to a Treatment group. The treatment consisted of using a computerized device (a Mandometer) during lunchtime to monitor food intake, rate of eating, and satiety.…”
Section: Ghrelin Levels)mentioning
confidence: 99%